The Future of Land Warfare - O'Hanlon, Michael (Brookings Institution Press, 2015)
In today's U.S. defense policy debates, big land wars are out. Drones, cyber weapons, special forces, and space weapons are in. Accordingly, Pentagon budget cuts have honed in on the army and ground forces: this, after the long wars in Iraq and Afghanistan, seems like an appealing idea. No one really wants American boots on the ground in bloody conflicts abroad. But it is not so easy to simply declare an end to messy land wars. A survey of the world's trouble spots suggests that land warfare has more of a future than many now seem to believe. In The Future of Land Warfare, Michael O'Hanlon offers an analysis of the future of the world's ground forces.